2018
DOI: 10.1016/j.fct.2018.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Circulating zearalenone and its metabolites differ in women due to body mass index and food intake

Abstract: The environmental estrogen, zearalenone (ZEA), is found in the food supply from Fusarium fungal contamination in grains and sometimes used as a growth promoter for beef cattle. Long-term exposure to ZEA and its metabolites may present health risk due to higher estrogenic activity. Serum ZEA metabolites were measured to determine the exposure and the association with food intake in 48 overweight/obese women (52 ± 9 years). The free and conjugated ZEA indicated the highest detection rate of all the metabolites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
(58 reference statements)
0
19
0
1
Order By: Relevance
“…In addition, some authors have added an enzymatic de-conjugation method to evaluate phase II metabolites. Plasma or serum samples were incubated with β-glucuronidase, or β-glucuronidase/sulfatase at 37 • C overnight, then the selected extraction procedure was applied [55,64,68,69].…”
Section: Mycotoxin Determination In Human Blood Plasma and Serummentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, some authors have added an enzymatic de-conjugation method to evaluate phase II metabolites. Plasma or serum samples were incubated with β-glucuronidase, or β-glucuronidase/sulfatase at 37 • C overnight, then the selected extraction procedure was applied [55,64,68,69].…”
Section: Mycotoxin Determination In Human Blood Plasma and Serummentioning
confidence: 99%
“…The introduction of Ultra-LC (UHPLC), characterized by uniform column packing material with a particle size of less than 2-3 µm and new pumps and detectors, has represented an improvement, given that it achieves shorter run times, reduces solvent consumption and improves chromatographic resolution and efficiency. UHPLC was reported in 42.8% of the chromatographic methods summarized in this review [48,53,58,64,65,68,69,[81][82][83].…”
Section: Mycotoxin Determination In Human Blood Plasma and Serummentioning
confidence: 99%
See 2 more Smart Citations
“…Zearalenone (ZEA) is a non‐steroidal, oestrogenic metabolite of Fusarium fungi (Belhassen et al, ; Othmen, Golli, Abidessefi, & Bacha, ). Zearalenone and its derivatives are widely distributed in rice, wheat and other crops, and these residues in meat and dairy products could pose health risks to humans (Mauro et al, ; Yang et al, ). Studies have shown that the strong oestrogenic and anabolic activities of ZEA induced serious alterations in the reproductive system of laboratory animals and farm livestock such as vulvar swelling, mammary glands hyperplasia, uterine enlargement, and even uterine, vaginal and rectal prolapse (Belli et al, ; Hewitt, Girgis, Brash, & Smith, ; Jiang et al, ).…”
Section: Introductionmentioning
confidence: 99%